Penerapan Kurikulum Merdeka Dalam Pembelajaran Sejarah di Sekolah Menengah Atas Negeri 1 Alalak - Siti Raihanah; Rochgiyanti; Syaharuddin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study has a background regarding the implementation of the Independent Curriculum in history learning. Indonesia has experienced a long learning crisis, to overcome this the Minister of Education is trying to get out of the learning crisis by changing the curriculum. The purpose of the study is to analyze the implementation of history learning using the Independent Curriculum at SMA Negeri 1 Alalak. The method used in this study is a qualitative descriptive method. Data collection techniques through several stages of observation, interviews, and document studies. Sampling of data sources was carried out by purposive sampling. The validity of the data in the study will use triangulation techniques. The results of the study show that the Independent Curriculum is used as a solution to recover from the learning crisis and is not free from other problems in implementing the new curriculum. Then for its implementation it has gone well, but teachers still have difficulty in adjusting to the interests and needs of students, The conclusion of this study examines the Implementation of the Independent Curriculum in history learning has gone well and is implemented by classes X and XI. Teachers still need adjustments regarding the curriculum, teachers need to know the learning style needed and need to take part in a lot of training and take part in the history MGMP in order to share with other school teachers.